GCRFP - PAGE REPLACEMENT FOR SOLID STATE DRIVE USING GHOST-CACHE - Wahyu Suadi; Supeno Djanali; Waskitho Wibisono; Radityo Anggoro; Ary Mazharuddin Shiddiqi (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2020)
State Drive (SSD) is an alternative to data storage that is popular today, widely used as a media cache to speed up data access to the hard disk (HDD). This paper proposes page replacement technique on SSD cache that used frequency and recency parameter, alternately. The algorithm is selected adaptively based on trace input. This method helps to overcome changes in access patterns while minimizing the number of write processes to SSD. The proposed algorithm can choose a replacement technique that suits the user access pattern so that it can bring a better hit rate. The proposed algorithm is also integrated with the ghost-cache mechanism so that the reduction in the number of writing processes to SSD is significant. The experiment runs using a real dataset, describing trace of data read, and data write taken from real usage. The trial shows that the proposed algorithm can give good results compared to other similar algorithms.